Insights into protist diversity and biogeography in intertidal sediments sampled across a range of spatial scales. (19th November 2019) - Pan, Yongbo; Yang, Jun; McManus, George B; Lin, Senjie; Zhang, Wenjing
Abstract: The relative importance of different ecological processes that shape community structure is a central but poorly understood topic in protist ecology. This study used an 18S rRNA gene sequencing approach to examine the relative contributions of environmental selective (environmental filtering) and neutral processes (dispersal and ecological drift) in the community assembly of three diverse protist groups (Bacillariophyta, Cercozoa, and Ciliophora) from intertidal sediment samples spanning a geographical distance up to 12, 000 km. All three protist communities exhibited similar and distinct biogeographical patterns, and followed strong distance–decay relationships at continental scale (ca. 12, 000 km), regional scale (ca. 1500 km), and local scale (ca. 50 km). Network analysis showed that temperature, salinity, nitrite and nitrate nitrogen, total nitrogen, and 0.1–0.25 mm grain size together associated with 60.8%, 55.5%, and 50.0% of the OTUs, which represented 68.1%, 58.5%, and 59.2% of sequence abundances for Bacillariophyta, Cercozoa, and Ciliophora co‐occurrence networks, respectively, indicating that these environmental variables played the central roles in influencing community composition. On the other hand, a neutral community model explained 73.6%, 64.2%, and 70.2% of community variation for Bacillariophyta, Cercozoa, and Ciliophora, respectively. More importantly, variation partitioning and partial Mantel tests showed that environmental selection exhibited a slightly greater influence on Ciliophora compared to spatial factors, but both components were roughly equivalent in Bacillariophyta and Cercozoa communities. Taken together, these results demonstrate that both environmental selection and neutral processes play important roles in creating the biogeographical patterns of protist communities in intertidal sandy beach ecosystems.